Undirected Sucrose Efflux Mitigation by the FT-Like SP6A Preferentially Enhances Tuber Resource Partitioning - van den Herik, Bas; ten Tusscher, Kirsten (Frontiers in Plant Science, 2022)
Yield of harvestable plant organs depends on overall photosynthetic output and the subsequent distribution of the produced assimilates from source leaves across different sink organs. In this work we aim to obtain, using a two-sink transport model, mechanistic understanding of how the interplay between sink and pathway properties together determine sink resource partitioning. As a working example, we analyzed the partitioning of resources within potato plants, investigating the determinants of tuber sink yield. Our results indicated that, contrary to earlier work, with a spatially explicit biophysically detailed model, transport pathway properties significantly affect sink resource partitioning within the physiologically relevant domain. Additionally, we uncovered that xylem flow, through its hydraulic coupling to the phloem, and sucrose efflux along the phloem, also significantly affected resource partitioning. For tubers, it is the cumulative disadvantage compared to sink leaves (distance, xylem flow and sucrose efflux) that enables an undirected SP6A-mediated reduction of sucrose-efflux to preferentially benefit tuber resource partitioning. Combined with the SP6A-mediated sink strength increase, undirected SP6A introduction significantly enhances tuber resource partitioning.